Increase of cardiac autoantibodies against beta-2-adrenergic receptor during acute cellular heart transplant rejection - Salbach, Christian; Schlegel, Philipp; Stroikova, Vera; Helmschrott, Matthias; Müller, Anna-Maria; Weiß, Christel; Giannitsis, Evangelos; Frey, Norbert; Raake, Philip; Kaya, Ziya (Transplantation, 2024)
Background. - Acute cellular rejection (ACR) in heart transplant (HTx) recipients may be accompanied by cardiac cell damage with subsequent exposure to cardiac autoantigens and the production of cardiac autoantibodies (aABs). This study aimed to evaluate a peptide array screening approach for cardiac aABs in HTx recipients during ACR (ACR-HTx). - Methods. - In this retrospective single-center observational study, sera from 37 HTx recipients, as well as age and sex-matched healthy subjects were screened for a total of 130 cardiac aABs of partially overlapping peptide sequences directed against structural proteins using a peptide array approach. - Results. - In ACR-HTx, troponin I (TnI) serum levels were found to be elevated. Here, we could identify aABs against beta-2-adrenergic receptor (β-2AR: EAINCYANETCCDFFTNQAY) to be upregulated in ACR-HTx (intensities: 0.80 versus 1.31, P = 0.0413). Likewise, patients positive for β-2AR aABs showed higher TnI serum levels during ACR compared with aAB negative patients (10.0 versus 30.0 ng/L, P = 0.0375). Surprisingly, aABs against a sequence of troponin I (TnI: QKIFDLRGKFKRPTLRRV) were found to be downregulated in ACR-HTx (intensities: 3.49 versus 1.13, P = 0.0025). A comparison in healthy subjects showed the same TnI sequence to be upregulated in non-ACR-HTx (intensities: 2.19 versus 3.49, P = 0.0205), whereas the majority of aABs were suppressed in non-ACR-HTx. - Conclusions. - Our study served as a feasibility analysis for a peptide array screening approach in HTx recipients during ACR and identified 2 different regulated aABs in ACR-HTx. Hence, further multicenter studies are needed to evaluate the prognostic implications of aAB testing and diagnostic or therapeutic consequences.
Gesehen am 19.11.2024